Shodaqoh Sampah Usia Dini : Implementasi Program Shodaqoh Sampah pada Pendidikan Usia Dini Wanjati Junior Pandaan Pasuruan - Amang Fathurrohman; M. Dayat; Syukur Sugeng Apriwiyanto; Mulyono Wibisono (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Waste issues in various regions, especially in Pandaan Pasuruan do not go down well. Pasuruan Regency Government still has limited ability in waste management. Therefore, the community of Women Jatianom (Wanjati) since 2012 has initiated the establishment of ECEP (Early Childhood Education Program/PAUD)Pro-Environment Wanjati, one of them by developing the program Early Age alms. Approach that is done with integrated community development that has been done since 2012, then obtained the result of environmental hygiene is one of the community needs. By doing environmental education from an early age, children from an early age already understand and apply in everyday life the principles of love environment in accordance with the teachings of Islam. The positive impact of this program also encourages ECEP/PAUD institutions to modify the curriculum to become more integrated between extracurricular activities and daily learning process. In addition, with the education of the character of love for the environment early on their children can give impact to parents to be more participative in maintaining the environment around them by managing the waste become more useful and valuable for and share knowledge among pupil through the